Th17 cells: a prognostic marker for MS rebound after natalizumab cessation? - Haas, Jürgen; Schneider, Katharina; Schwarz, Alexander; Korporal-Kuhnke, Mirjam; Faller, Simon; Jarius, Sven; Wildemann, Brigitte (Multiple sclerosis journal, 2017)
Background:Multiple sclerosis (MS) patients are at risk of renewed disease activity after discontinuing natalizumab (NAT) treatment.Objective:Assessing the implication of T helper 17 (Th17) cells in MS reactivation after NAT cessation.Methods:We monitored frequencies of Th17 cells and interleukin (IL)-17 cytokine levels in blood samples of 57 MS patients, without, during, and after NAT exposure.Results:Frequencies of both Th17 cells and, in part, also IL-17 levels, in peripheral blood increased under prolonged NAT therapy, returned to baseline after NAT withdrawal and became almost undetectable in blood samples of individuals who experienced relapses during the wash-out phase.Conclusion:Assessing the Th17-cell/IL-17 axis might help to predict rebound MS activity after NAT withdrawal.